Labor market for young people in Colombia (2017)
This essay reveals the current panorama of the labor market conditions for young people in Colombia, based on supply and demand. In addition, the evolution of the youth labor market in recent years through occupancy and unemployment rated is presented. We explore the idea of the role of the National government in the generation of decent employment and in terms if proposals, this work also seeks, from the review of the main lines of action in Colombia, to find alternatives that improve the employment situation for young people.